Structural Inheritance Controls Strain Distribution During Early Continental Rifting, Rukwa Rift - Kolawole, Folarin; Phillips, Thomas B.; Atekwana, Estella A.; Jackson, Christopher A.-L. (Frontiers in Earth Science, 2021)
Little is known about rift kinematics and strain distribution during the earliest phase of extension due to the deep burial of the pre-rift and earliest rift structures beneath younger, rift-related deposits. Yet, this exact phase of basin development ultimately sets the stage for the location of continental plate divergence and breakup. Here, we investigate the structure and strain distribution in the multiphase Late Paleozoic-Cenozoic magma-poor Rukwa Rift, East Africa during the earliest phase of extension. We utilize aeromagnetic data that image the Precambrian Chisi Shear Zone (CSZ) and bounding terranes, and interpretations of seismic reflection data to show that, during the earliest rift phase (Permo-Triassic ‘Karoo’): (1) the rift was defined by the Lupa border fault, which exploited colinear basement terrane boundaries, and a prominent intra-basinal fault cluster (329°±9.6) that trends parallel to and whose location was controlled by the CSZ (326°); (2) extensional strain in the NW section of the rift was accommodated by both the intra-basinal fault cluster and the border fault, where the intra-basinal faulting account for up to 64% of extension; in the SE where the CSZ is absent, strain is primarily focused on the Lupa Fault. Here, the early-rift strain is thus, not accommodated only by border the fault as suggested by existing magma-poor early-rift models; instead, strain focuses relatively quickly on a large border fault and intra-basinal fault clusters that follow pre-existing intra-basement structures; (3) two styles of early-rift strain localization are evident, in which strain is localized onto a narrow discrete zone of basement weakness in the form of a large rift fault (Style-1 localization), and onto a broader discrete zone of basement weakness in the form of a fault cluster (Style-2 localization). We argue that the CSZ and adjacent terrane boundaries represent zones of mechanical weakness that controlled the first-order strain distribution and rift development during the earliest phase of extension. The established early-rift structure, modulated by structural inheritance, then persisted through the subsequent rift phases. The results of our study, in a juvenile and relatively well-exposed and data-rich rift, are applicable to understanding the structural evolution of deeper, buried ancient rifts.